2016
DOI: 10.1017/s0376892915000417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential effectiveness of alternative management scenarios in ape habitat

Abstract: SUMMARYChoosing appropriate management strategies and effective conservation actions requires information about the future consequences of current conservation actions; however, this crucial information is rarely available to conservation planners. This study applies scenario planning and agent-based modelling (ABM) to assess the potential impact of alternative management strategies on future suitability and functional connectivity of Cross River gorilla (CRG) habitat in the Nigeria–Cameroon border region. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, building resistance within protected areas will never be sufficient alone. If human pressure on a protected area is high and increasing, a protected area system will eventually collapse without interventions to mitigate or control human demands for natural resources in and around them (Imong, Kühl, Robbins, & Mundry, ). Although, research showing how socio‐economic context or development actually affect pressure on protected areas is rare, a study in Liberia has shown that areas with increased literacy have higher densities of chimpanzees (Junker, Boesch, Mundry, et al, ).…”
Section: Increased National Commitmentmentioning
confidence: 99%
“…However, building resistance within protected areas will never be sufficient alone. If human pressure on a protected area is high and increasing, a protected area system will eventually collapse without interventions to mitigate or control human demands for natural resources in and around them (Imong, Kühl, Robbins, & Mundry, ). Although, research showing how socio‐economic context or development actually affect pressure on protected areas is rare, a study in Liberia has shown that areas with increased literacy have higher densities of chimpanzees (Junker, Boesch, Mundry, et al, ).…”
Section: Increased National Commitmentmentioning
confidence: 99%
“…179 Modeling showed that conservation management strategies that focused on both law enforcement and behavior change of local human populations are needed to ensure future growth of this subspecies. 190 Conservation efforts should focus on law enforcement, land-use planning, and engagement with the private sector. 181,187 Research, both long term studies and large scale surveys, makes a valuable contribution to conservation efforts by providing information on ecological needs and population dynamics of gorillas.…”
Section: Gorillas and Human Evolutionmentioning
confidence: 99%
“…We selected this community because of prior established relationships from previous research projects ( Andersson Djurfeldt et al 2017), their previous involvement in REDD+ workshops, and since the community forest borders the Afi River forest reserve and the Afi Mountain wildlife sanctuary, a known habitat for the three endangered species of primates (Dunn et al 2014). Hunting is a very common activity in the area and combined with habitat loss and fragmentation, it is an increasing threat to many species, particularly the Cross-River gorilla (Effiom et al 2013;Dunn et al 2014;Bergl et al 2016;Imong et al 2016).…”
Section: Biodiversity Conservation and Redd+ In Nigeria And Cross Rivmentioning
confidence: 99%